LB1.1 Insights into the evolution of syphilis spirochetes within at-risk populations: sequence variation of outer membrane protein β-barrel domains in clinical samples. (8th July 2017) - Radolf, Justin; Kumar, Sanjiv; Smajs, David; Dey, Abhishek; Anand, Arvind; Ledoyt, Morgan; Karanian, Carson; Cruz, Adriana; Ramirez, Lady; Caimano, Melissa; Salazar, Juan
Abstract : Introduction: Outer membrane proteins (OMPs) play critical roles in disease pathogenesis and are vaccinogens. Topologic characterisation of surface-exposed β-barrels of Treponema pallidum ( Tp ) Nichols rare OMPs enabled a novel strategy to assess sequence diversity and evolution of Tp in geographically diverse locations. Methods: Through early 2017, sequences encoding TprC (TP0117), TprD (TP0131), and BamA (TP0326) β-barrels were amplified from secondary syphilis patients from Cali (n=16) and swabs from patients in San Francisco (SF, n=6) and Czech Republic (CZ, n=9). Strains were assigned to the Nichols or SS14 clade based on tp0548 and/or tp0558 sequences. Results: 23 assignable CZ and Cali strains belonged to either the SS14 or Nichols clade (SS14 predominant), while all 6 SF strains belong to the SS14 clade. Sequence diversity at the three OMP loci was greatest in Cali, with evidence of recombination within tprC and bamA alleles, as well as between strains and clades at all 3 genetic loci. SF strains contained nearly identical sequences at all 3 genetic loci. The SS14 and Mexico A reference strains, both belonging to the SS14 clade, have identical tprDs ( tprD2 ) but different tprC and bamA alleles. Mexico A tprC s were common at all three geographic locations, including Nichols clade strains from Cali. Mexico A bamA s were prevalent in Cali and SF, while CZ SS14 clades contained only SS14 bamA s. OMP sequences were obtained from all three loci in 7 of 8 Nichols clade strains. Of these 7, only 1 matched the Nichols reference strain, while the other 6 contained Mexico A alleles in at least 1 OMP locus. Of the 21 SS14 clade strains, 10 contained Mexico A alleles at all 3 loci; 2 contained Mexico A trpCs and Nichols bamAs ; and 9 contained Mexico A tprCs and SS14 bamAs . Conclusion: OMP loci are evolving independently within Tp . Recombination of OMP sequences appears to be occurring between Tp strains and clades within patients. Mexico A OMP alleles are circulating widely among Tp strains. These findings have major ramifications for syphilis vaccine development.